Prevalence of Phenylthiocarbamide (PTC) Taste Sensitivity and Colour Blindness in Tengger Tribe Population, Ranupani Village, Senduro, Lumajang - Oktarianti, Rike; Putra, Iguh Widigda; Arofa, Resmining Mega; Lelono, Asmoro (BERKALA SAINSTEK, 2021)
The taste of sensitivity of phenylthiocarbamide (PTC), is autosomal dominant trait inherited while the colour blindness is a sex linked genetic trait on the X chromosome. The purpose of this study was to determine the distribution of taster and non taster phenotypes, prevalence of color blindness, frequency of taster and non taster alleles, and frequency of color blind alleles, as well as pedigree analysis in non taster and color blind families. The research was conducted on the Tengger tribe, in Ranupani village, Senduro, Lumajang. Determination of the sample is carryout randomly. Detection of the ability to taste PTC was respondents to taste the PTC solution from the lowest concentration of 0.32mg/L (P13) to the highest concentration of 1300 mg/L (P1). Color blindness detection by the Ishihara method. The results of the study showed that the distribution of the taster was 98.1% while the non-taster was 1.9%. The allele frequency of the dominant taster (T) was 0.86 and the recessive allele non taster (t) is 0.14. The prevalence of color blindness in the population of the Tengger tribe was 0.63% and the allele frequency for color blindness was 0.013. The pedigree analysis of non taster family showed that non taster individuals were born from taster couple (Tt) or from couple of non taster (tt) with tasters (Tt) heterozigot. While the pattern of inheritance of color blindness was criss-cross inheritance pattern, which is passed from mother to son.